Leviathan - Westerfeld, Scott (Westerfeld, Scott. Leviathan trilogy., 2009)
In an alternate 1914 Europe, fifteen-year-old Austrian Prince Alek, on the run from the Clanker Powers who are attempting to take over the globe using mechanical machinery, forms an uneasy alliance with Deryn who, disguised as a boy to join the British Air Service, is learning to fly genetically-engineered beasts.